Clinical outcomes of full arthroscopic combined latissimus dorsi and teres major transfers for irreparable subscapularis tears - Bo Taek Kim; Luis Alfredo Miranda; Chang Hee Baek; Jung Gon Kim; Luis Leoncio Temoche Diaz; Gyu Rim Baek; Jean Kany (Journal of Experimental Orthopaedics, 2025)
Abstract Purpose Managing irreparable subscapularis tears poses a challenge. Traditionally, pectoralis major transfer has been the gold standard, but alternative methods including anterior latissimus dorsi (LD) and teres major (TM) tendon transfers have shown promise. This study evaluates the clinical outcome of full arthroscopic combined LDTM transfers for irreparable subscapularis tears. Methods Patients with irreparable subscapularis tears who underwent full arthroscopic combined LDTM transfers from October 2020 to August 2022 were retrospectively reviewed. The inclusion criteria comprised failure of conservative treatment, irreparable subscapularis tears (Lafosse grade ≥ 4), and no to minimal glenohumeral arthritis (Hamada grade < 3). The exclusion criteria included patients with missing clinical data. Clinical assessments included the visual analogue scale (VAS), the Constant score, the Subjective Shoulder Value (SSV), active range of motion (ROM), and internal rotation strength. A total of 11 patients met the inclusion criteria and were included in this study. Results Out of 14 patients, 11 met the inclusion criteria, with a mean age of 65.9 ± 6.0 years and a follow‐up duration of 25.9 ± 6.2 months. Postoperative results demonstrated significant pain relief, with the VAS score improving from 8.1 ± 0.9 to 2.1 ± 2.1 (p < 0.001). Functional outcomes improved significantly, with the Constant score increasing from 29.9 ± 3.9 to 62.6 ± 15.9 (P < 0.001) and the SSV improving from 25.3 ± 8.7 to 66.5 ± 20.1 (p < 0.001). ROM significantly increased in forward elevation, abduction, and internal rotation, while internal rotation strength also improved significantly. There were no complications or progression of arthritis observed. Conclusion Full arthroscopic combined LDTM transfer demonstrates promising clinical and radiological short‐term outcomes for patients with irreparable subscapularis tears. The procedure resulted in substantial improvements in pain relief and functional outcomes, particularly in internal rotation for both ROM and strength. Importantly, no significant complications or progression of glenohumeral arthritis were observed by the final follow‐up. Level of Evidence Level IV, retrospective case series.